Etnobotani Masyarakat Lokal, Struktur Anatomi Jenis Pandan (Pandanaceae) Bermanfaat di Jawa Timur - Jati Batoro; Serafinah Indriyani; Brian Rahardi (Research Journal of Life Science, 2015)
Along with the development of culture, both traditional and biotechnology, the use of pandan, as can be found either in the community, traditional markets, experiencing a shift which was replaced by other materials, such as by plastic straps, caps from fabric. Ethnobotany study done by collecting a "ethnodirect sampling" technique with direct or semi-structural interviews. The method is carried out at pandan anatomy including: methods for extracting fiber, making transverse and longitudinal leaf preparations, measurements of leaf length and fiber strength and making preparations transversal and longitudinal of supporting root. The long term goal of this study is to obtain a data base of pandan (Pandanaceae) that can later be used to perform resource management in pandan (Pandanaceae) to its preservation in East Java, thus supporting ecological functions and the resulting types are also cultivating other Pandan also potentially. The short term goal is to get the kind of pandan (Pandanaceae) is useful to be developed as a craft that can later be used to improve the economy of East Java community through anatomical structures. The three types of pandan namely P. tectorus, P. labyrinthicus and P. furcatus has the potential to be developed as a base for the manufacture of rope and handicrafts. The potential of plant-based crafts from fiber can still be developed on the craft of Pandanus.